ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MARKET SHARE BANK SYARIAH - Aulia Rahman (Program Pascasarjana UIN Sumatera Utara, 2016)
This study aims to determine the factors that affect the market share of Islamic banks. The sample used is data NPF, ROA, CAR, SBIS of the market share of Islamic banks from January 2010 to December 2015. The approach used in this study is a quantitative research approach with VAR analysis.From the research, the authors conclude that NPF variables, ROA, CAR and SBIS affect the market share of Islamic banks. In the short term or the beginning of the observation period BOPO has the most dominant influence. While in the long term or the end of the observation period NPF has the most dominant influence on the Market Share of Islamic Banks compared to other variable that is 29.02%. SBI variables have an influence on the market share of Islamic banks amounted to 15.68% and CAR have an influence on the market share of Islamic banks amounted to 2.97% at the end of the observation period. Thus, it can be seen that the variables that most influence in the long term is a variable NPF